2020
DOI: 10.3389/fpsyg.2020.581162
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Fit Demonstrates That Prohibitive Voice Does Not Lead to Low Performance Evaluation

Abstract: Voice behavior, the extra-role behavior of employees based on their sense of responsibility, plays an important role in organizational development. Research shows that an employee’s voice can have a positive impact on both the quality of decision-making and organizational performance. This study explores the relationship between the prohibitive voice and employees’ safety performance based on the theory of regulatory fit. The study examined 372 employees and their leaders in the Ningxia Hui Autonomous Region o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 43 publications
3
5
0
Order By: Relevance
“…The results indicated that the effect of prohibitive voice on communication effectiveness was not significant. Our finding is similar to past research which reported that the impact of prohibitive voice was weak (e.g., Burris et al., 2022 ; Chamberlin et al., 2017 ; Huang et al., 2018 ; Lam et al., 2022 ; Yang, 2020 ). For example, Chamberlin's et al.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The results indicated that the effect of prohibitive voice on communication effectiveness was not significant. Our finding is similar to past research which reported that the impact of prohibitive voice was weak (e.g., Burris et al., 2022 ; Chamberlin et al., 2017 ; Huang et al., 2018 ; Lam et al., 2022 ; Yang, 2020 ). For example, Chamberlin's et al.…”
Section: Discussionsupporting
confidence: 92%
“…This finding demonstrates that situational factors (i.e., hindrance stressor) and employees' characteristics (i.e., work-based construal level) can determine the effect of prohibitive voice on communication effectiveness. In support of our findings, previous voice literature also documented that there were many moderators which can change the outcomes of voice behavior (e.g., Brykman and Raver, 2021 ; Hung et al., 2012 ; McClean et al., 2022 ; Yang, 2020 ). For instance, Yang's (2020) empirical research showed that prevention regulatory focus fit can enhance the positive association between prohibitive voice and safety performance.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations